INDUKSI TUNAS DARI NODUL KRISAN KULO DALAM MEDIA MURASHIGE DAN SKOOG YANG DIBERI SITOKININ - Tilaar, W.; Rantung, J.; Tulung, S. (EUGENIA, 2015)
ABSTRACT The kulo chrysanthemum variety is a North Sulawesi local variety characterized by large white flowers.  The new variety was introduced barely two years ago, yet it has gained considerable popularity among flower farmers in Tomohon City as well as in Manado, Tondano, and around the Minahasa and North Minahasa regencies. The growing interest in this particular variety has increased the demand for nursery stock resulting in a shortage of supply.  The conventional plantlet propagation method i.e. one seed to grow one plant, is deemed very time consuming and has poor plantlet yield.   It is therefore necessary to explore other plantlet propagation methods that can produce high yield in a relatively short period of time. One of the best techniques for plantlet propagation is tissue culture.  The success of tissue culture in producing high plantlet yield is determined by the use of appropriate plant growth regulators. Accurate concentrations of growth regulators are vital in achieving an optimum yield.  Consequently, determining the exact concentrations is a major issue in the tissue culture method.    Cytokinins are commonly used as growth regulators in shoot and plantlet propagations.  However, different types of cytokinins may have different effects on shoot generation from the nodal explants used in particular in vitro propagations.  The kulo chrysanthemum variety has never been propagated using the nodal explant tissue culture technique and may respond differently than other varieties.  Therefore, it is essential to determine which types of cytokinins are most suited to stimulate its shoot and plantlet propagations. Keywords:  propagation, chrysanthemum nodes, murashige, skoog, BAP, kinetin, and NAA